Utilization of landsat-8 data for lithological mapping of basement rocks of plateau state north central Nigeria - Amusuk, D. J. (International Society for Photogrammetry and Remote Sensing, 2016)
This paper utilized the Landsat-8 image data to map the lithology's of Plateau state north central Nigeria. This is includes the rocks, with particular emphasis on their description and classification. We are living in geologic times and sciences that provide adequate knowledge of the natures of what we live on so as to preserve and have means of sustaining human life. Plateau State is covered by four scenes of Landsat Data, and to describe the lithology's, each scene was processed to produce images. Two different false colour composite images of Landsat-8 (FCC 7, 5 and 3 and BR composites) in RGB were generated and used for the production of 1:100,000 geological map of the study area. The identification of predominant biotitic granitic rocks was revealed and that are distributed along the Jos-Bukuru complex and underlying almost half of the entire state. Moreover, the other rock complexes such as basalts and rhyolites volcanic rocks were also discriminated. This study indicates that Landsat-8 image data has great capability to discriminate lithological units and the production of up-to-date geological maps at regional scale and could be applicable in other regions of the African continent.